Nurses' perception and self-confidence of family presence during cardiopulmonary resuscitation in Saudi Arabia - Aisha Alhofaian; Safiah Mesfer Almuntashiri; Manar Hisham Bamufleh; Shimaa Ahmad Al-Faraj; Salma Abed Alharbi; Afnan Tunsi; Marym M Alaamri (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Researchers have investigated the presence of families during cardiopulmonary resuscitation (CPR) to determine its benefits and barriers and the points of view of healthcare professionals, patients, and families. Family presence during resuscitation (FPDR) is debatable. Many professional health organizations worldwide, such as the Emergency Nurses Association, have suggested that healthcare facilities implement rules and policies that encourage the attendance of families and relatives during CPR. However, this does not consider the nurses' points of view or self-confidence during FPDR. The main aim of this study is to evaluate nurses' perceptions and self-confidence related to family presence during CPR in Saudi Arabia.MATERIALS AND METHODS: This descriptive correlation study was conducted between March and April 2022 at King Abdul Aziz University Hospital in Jeddah. A survey was completed by participants to collect their sociodemographic data. The relationship between Family Presence Risk-Benefit Scale (FPS-BS) and the Family Presence Self-Confidence Scale (FPS-CS) was analyzed using Pearson's correlation test.RESULTS: The study's participants consisted of 147 nurses. Regarding the FPDR, nurses had a moderately positive perception and level of confidence. Moreover, the level of self-confidence varied significantly by age group and years of experience. The results of the Pearson correlation indicated that there was a significant association between FPS-CS and FPR-BS (r = 0.221, P < .001). When implementing FPDR, nurses who see more benefits from it are more confident.CONCLUSION: According to the findings, the nurses who felt more comfortable including patients' families in resuscitation efforts also saw FPDR as having more advantages. FPDR has several effects on the healthcare team providing CPR. Nursing leaders should develop policies for their teams and instruct nurses and other healthcare professionals. Considering the clear benefits of clinical practice and family involvement in resuscitation, it is suggested to give this experience first using simulation and role-playing.